Brain Abscesses: An Overview in Children - Krzysztofiak, Andrzej; Zangari, Paola; De Luca, Maia; Villani, Alberto (Journal of Pediatric Infectious Diseases, 2019)
Brain abscesses in infants and children might be life threatening if not managed properly. They occur more frequently in the first two decades of life despite the reduced incidence of sinus and ear infections in pediatrics. The features of brain abscess in terms of location, pathogens, and symptoms depend on age and thus on predisposing factors. In infants and toddlers, bacterial meningitis or bacteremia is the major cause, and in older children, immunosuppression and cyanotic congenital heart diseases are common predisposing factors. The therapeutic management of brain abscesses involves a multidisciplinary team, including infectious disease specialist, neurosurgery, neuroradiology, and neurology. A prompt and long-term antimicrobial therapy is the mainstay of treatment, often associated with surgical drainage. These changes in the management have significantly improved the prognosis of patients with brain abscesses over the past 50 years.
Keywords: brain abscess; children; management